Exploring Online Pedagogical Practices for Enhancing Transfer of Learning in Higher Education - Tamara Galoyan; Kristen Betts; Brian Delaney; Mariette Fourie (Online Learning, 2021)
Institutions of higher education play a critical role in bridging academia and workforce, yet college students find it challenging to transfer their learning across and beyond instructional formats, including online, hybrid, and face-to-face. The goals of this exploratory, sequential, mixed-methods study were to (1) explore graduate students’ conceptualizations of transfer, and (2) examine online pedagogical practices for enhancing transfer. Participants included students enrolled in a full-time online graduate degree program in education at a private university in the Mid-Atlantic USA. Findings from the qualitative phase with seven semi-structured interviews were used to design a survey study with 68 graduate students to explore their perceptions of effective online pedagogical practices for enhancing transfer. This study is significant since its findings revealed a number of online practices that instructional designers and faculty can use to optimize learning and transfer in higher education.